Mars Exploration a Step Forward - Pezzella, Giuseppe; Viviani, Antonio (IntechOpen, 2020)
More than 50 years after the Mariner 4 flyby on 15 July 1965, Mars still represents the next frontier of space explorations. Of particular focus nowadays is crewed missions to the red planet. Over three sections, this book explores missions to Mars, in situ operations, and human-rated missions. Chapters address elements of design and possible psychological effects related to human-rated missions. The information contained herein will allow for the development of safe and efficient exploration missions to Mars.